Some Neutrosophic Ideals of BF-algebras - Ibrahim, A.; Kavitha, B. (Journal of Informatics and Mathematical Sciences, 2025)
In this paper, we introduce the notions of neutrosophic ideal and neutrosophic subalgebra of BF-algebra with suitable illustrations. Further, we discuss homomorphism and epimorphism mappings of neutrosophic ideals. Also, we introduce the definitions of a neutrosophic implicative ideal and a neutrosophic ideal of BF-algebras and investigate some of their properties.